The Effect of Work Environment and Work Motivation on Employee Performance with Work Satisfaction as an Intervening Variable at the Department of Energy and Mineral Resources Medan - Luthfi Al Idrus; Kiki Farida Ferine (International Journal of Management, Economic and Accounting, 2025)
Employees have an important role in realizing the overall department objectives, whether or not a department is successful depends on the performance of the employees themselves. Work Environment has a positive and significant effect on Employee Performance with a value of 0,371 and significant 0,045. Work Environment has a positive and significant effect on Work Satisfaction 0.840 and significant 0,000. Work Motivation has a positive and significant effect on Employee Performance with a value of 0,346 and significant 0,010. Work Motivation has a positive and insignificant effect on Work Satisfaction with a value of 0.130 and a significant 0,287. Work Satisfaction has a positive and significant effect on Employee Performance with a value of 0,274 and significant 0,020. Work Environment has a positive and insignificant effect on Employee Performance through Work Satisfaction with a value of 0,214 and significant 0,095. Work Motivation has a positive and insignificant effect on Employee Performance through Work Satisfaction with a value of 0,033 and significant 0,165.